Effect of Fe2O3 additions on sinterability of Konya dolomite of Turkey - Yeprem, HA; Hübner, H (TRANS TECH PUBLICATIONS LTD, 2004)
The sintering behaviour of dolomite extracted from a mine in the Konya-Sille-Ecmel region of Turkey was studied. Sintering tests were performed at different sintering temperatures (1600degreesC, 1650degreesC and 1700degreesC) and soaking times (2, 4, 6 hours) on powders which were either pure or contained selected amounts of iron scale of a thickness below 45 mum (98.66 wt% Fe2O3). The bulk density and the apparent porosity of the sintered products were examined which turned out to be dolomite (doloma), and the differences obtained under various sintering conditions were explored. The study revealed the following results: (1) The sintering temperature of the raw dolomite was decreased by the addition of iron oxide, which is attributed to the formation of liquid phase. (2) The newly formed phases were found to sintered granule surfaces very well, resulting in a smaller influenced area and a higher resistance to hydration. Thus, the study has shown that the addition of iron oxide at a level that is small enough to avoid corrosion results in a sintering process that can be carried out at distinctly lower temperatures and in less time. This behaviour may encourage the use of domestic doloma.
Keywords: dolomite; doloma; sinterability; liquid phase; iron oxide; Materials Science